2014
DOI: 10.1007/s00431-014-2309-3
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of nebulized salbutamol, magnesium sulfate, and salbutamol/magnesium sulfate combination in moderate bronchiolitis

Abstract: Nebulized magnesium sulfate plus salbutamol may have additive effects for improving the short-term CSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 12 publications
3
47
0
1
Order By: Relevance
“…In a second small trial that enrolled patients with moderate bronchiolitis and compared nebulized magnesium, nebulized salbutamol, and nebulized magnesium sulfate/salbutamol combined, the only significant difference was the Wang severity score at 4 h, which favored the combined aerosol group compared with the nebulized magnesium alone group (P < .05). 22 Given the uncertainties about clear-cut efficacy for-as well as the amount of magnesium delivered by-nebulizing magnesium for the treatment of asthma, 23 we chose to use IV magnesium for the present study. Patients needing hospital admission in the 2 wk after discharge 4 (5.2) 1 (1.2) .20…”
Section: Discussionmentioning
confidence: 99%
“…In a second small trial that enrolled patients with moderate bronchiolitis and compared nebulized magnesium, nebulized salbutamol, and nebulized magnesium sulfate/salbutamol combined, the only significant difference was the Wang severity score at 4 h, which favored the combined aerosol group compared with the nebulized magnesium alone group (P < .05). 22 Given the uncertainties about clear-cut efficacy for-as well as the amount of magnesium delivered by-nebulizing magnesium for the treatment of asthma, 23 we chose to use IV magnesium for the present study. Patients needing hospital admission in the 2 wk after discharge 4 (5.2) 1 (1.2) .20…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that nebulized magnesium sulfate plus salbutamol treatment were effective for improving the clinical scores of patients with bronchiolitis. 11 Our findings suggested that there may be a relationship between magnesium deficiency and bronchiolitis because of the good response of bronchiolitis patients to magnesium treatment.…”
mentioning
confidence: 53%
“…In our previous study, combination therapy with inhaled magnesium sulfate and salbutamol was significantly (p<0.05) more effective than treatment with inhaled magnesium sulfate or salbutamol alone for patients with acute bronchiolitis attack. 11 In recent years, the magnesium metabolism in asthma and bronchiolitis has been studied. Generally, in these studies magnesium sulfate was used for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Tracheal intubation (IV) (31) 30 mgÁkg À1 Laryngospasm (IV) (23,33,34) 15 mgÁkg À1 Bronchospasm (IV) (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) 50-100 mgÁkg À1 + 40-50 mgÁkg À1 Áh À1 Bronchospasm (nebulized) (47)(48)(49)(50)(51)(52)(53)(54)(55) 40 mgÁkg À1 or 150 mg (total dose) Antiadrenergic response Cardiopulmonary bypass (IV) (57-60) 25-50 mgÁkg À1 Long QT syndrome (IV) (61) 30-50 mgÁkg À1 + 5-20 mgÁkg À1 Áh À1 Neonatal pulmonary hypertension (IV) (63) 200 mgÁkg À1 + 20-150 mgÁkg À1 Áh À1 Pheocromocytoma (IV) (64) 30-50 mgÁkg À1 + 5-20 mgÁkg À1 Áh À1 Organ protection Neuroprotection (IV) (68-72) 250 mgÁkg À1 Áday À1 Myocardial protection (cardioplegia) (73,74) 40-80 mgÁkg À1 Hypomagnesemia Perioperative hypomagnesemia (IV) (58,59) 25-50 mgÁkg À1 AE 5-20 mgÁkg À1 Áh À1 alveolar concentration by 50% and the induction dose of propofol; it shortens the latency time until a bispectral index value <60 is reached; and it reduces ventilation requirements (tidal volume and respiratory rate) as metabolism decreases (O 2 consumption and CO 2 production) (2,6). Sevoflurane has certain excitatory effects on the central nervous system, which may be associated with increased seizure activity in children.…”
Section: Muscle Relaxationmentioning
confidence: 99%
“…Although more studies are needed in this line, current results suggest favorable cost-effectiveness; better side effect profile than IV MgSO 4 ; greater response in severe crisis and early treatment; and comparable efficacy to nebulized epinephrine, lower than nebulized beta-2 agonists and IV MgSO 4 , and higher when it is associated with nebulized beta-2 agonist. The recommended dosing regimen for nebulized MgSO 4 is 40 mgÁkg À1 or a total dose of 150 mg (47)(48)(49)(50)(51)(52)(53)(54)(55).…”
Section: Muscle Relaxationmentioning
confidence: 99%